2014
DOI: 10.1002/2014jd021550
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of aerosol optical depth retrieval using visibility data in China during the past 50 years

Abstract: that it reached a maximum value in summer with the average value between 0.34 and 0.36 for the whole China, while a minimum value was reached in winter with a mean value between 0.2 and 0.22. It is noted that the aerosol vertical profile was a sensitive factor to the inversion result. The root-mean-square error using Goddard Chemistry Aerosol Radiation and Transport aerosol profiles was increased 1.9 to 5.7 times than using the traditional three-segment profile in northwest, southwest, northeast, and northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 58 publications
4
35
0
Order By: Relevance
“…Lu et al (2010) [1973][1974][1975][1976][1977][1978][1979][1980] period, and southern China shows an even faster impairment (2.9 % yr −1 ) than the north (1.2 % yr −1 ). For the next 2 decades the 1/Vis increase slows down in both the south and the north, in accordance with other investigations using Vis and SSR data Luo et al, 2001;Wu et al, 2014). The south exhibits a slower (0.2 % yr −1 ) and less significant (p > 0.3) increase than the north (0.5-0.6 % yr −1 ).…”
Section: Trend Evaluationsupporting
confidence: 91%
See 1 more Smart Citation
“…Lu et al (2010) [1973][1974][1975][1976][1977][1978][1979][1980] period, and southern China shows an even faster impairment (2.9 % yr −1 ) than the north (1.2 % yr −1 ). For the next 2 decades the 1/Vis increase slows down in both the south and the north, in accordance with other investigations using Vis and SSR data Luo et al, 2001;Wu et al, 2014). The south exhibits a slower (0.2 % yr −1 ) and less significant (p > 0.3) increase than the north (0.5-0.6 % yr −1 ).…”
Section: Trend Evaluationsupporting
confidence: 91%
“…Historical Vis data from more than 3000 stations have been applied to characterize decadal trends in global aerosol optical depth (AOD) from 1973 to 2007 (Wang et al, 2009). Regional trend studies of Vis were also conducted for populated areas e.g., the US (Husar et al, 1981;Schichtel et al, 2001), Europe (Vautard et al, 2009) and China (Che et al, 2007;Chen and Wang, 2015;Lin et al, 2014;Wu et al, 2012Wu et al, , 2014, and the inferred trends were usually attributed to changes in anthropogenic emission. Another study employing Vis over desert regions (Mahowald et al, 2007) found an association of Vis with meteorology factors such as drought index (based on precipitation and temperature) and surface wind speeds.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has been used to obtain decadal time series of the aerosol optical thickness over the Netherlands and China (Boers et al, 2015;Wu et al, 2014). We examined the European Centre for Medium-Range Weather Forecasts reanalysis (ERA-Interim) data (Dee et al, 2011) for changes in the planetary boundary layer depth.…”
Section: Retrieval Of Aerosol Optical Thicknessmentioning
confidence: 99%
“…Apart from occasional sun photometer records (Ruckstuhl et al (2008), data on aerosol are often unavailable. However, recent studies by Wu et al (2014) and Boers et al (2015) have shown that it is possible to retrieve useful aerosol optical thickness data from surface visibility records. The principal idea behind both studies is almost 50 years old (Eltermann, 1970;Kriebel, 1978;Peterson and Fee, 1981; revived by the work of Wang et al, 2009) and asserts that clear-sky optical thickness is most often caused by aerosols residing in the planetary boundary layer, which can be characterized by the optical extinction at 550 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The result indicated that there was one upward trend pre-2008 (0.0003) and one downward trend post-2008 (−0.0005) for AOD in China during 2000-2015. The AOD values were higher in spring (0.410) than that in summer (0.370), autumn (0.260), and winter (0.340). Wu et al [31] analyzed the spatial and temporal variations of AOD values during 1960-2009 using the Multiangle Imaging Spectroradiometer (MISR) AOD records and meteorological measurements. The results showed that the AOD values over mainland China exhibited an increasing trend (0.004 year −1 ) during reconstructed the AOD values during 1993-2012 throughout China using a broadband extinction model, which showed good agreements with AERONET AOD values with RRMSE, MAE, and R of 0.101, 0.029, and 0.848, respectively.…”
Section: Introductionmentioning
confidence: 99%